2003
DOI: 10.1021/jf026042j
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Properties of Virgin Olive Oil Polyphenols:  Identification of Deacetoxy-ligstroside Aglycon as a Key Contributor to Pungency

Abstract: Polyphenols are an important functional minor component of virgin olive oils that are responsible for the key sensory characteristics of bitterness, pungency, and astringency. Polyphenols were isolated from virgin olive oils by using liquid/liquid extraction and then separated by using reverse phase HPLC followed by fraction collection. The sensory qualities of the isolated polyphenols were evaluated, and almost all fractions containing polyphenols were described as bitter and astringent. However, the fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
268
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(284 citation statements)
references
References 26 publications
12
268
0
4
Order By: Relevance
“…Polyphenols are responsible for some important sensory properties associated with wine. This complex and large family of molecules is responsible for production of taste sensations ranging from bitter to astringent and pungent depending upon the composition of the polyphenol in the food (Andrewes et al 2003, Preys et al 2006. It has been reported that higher concentrations of polyphenols, tannins and -epicatchins affect the perceived fl avour of cocoa favorably (Bonvehi andColl 1997, Misnawi et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols are responsible for some important sensory properties associated with wine. This complex and large family of molecules is responsible for production of taste sensations ranging from bitter to astringent and pungent depending upon the composition of the polyphenol in the food (Andrewes et al 2003, Preys et al 2006. It has been reported that higher concentrations of polyphenols, tannins and -epicatchins affect the perceived fl avour of cocoa favorably (Bonvehi andColl 1997, Misnawi et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Andrewes et al [137] assessed the relationship between polyphenols and olive oil pungency. p-HPEA-EDA was the key source of the burning sensation found in many olive oils.…”
Section: Sensory Properties Elicited By Phenols In Voomentioning
confidence: 99%
“…Since no prior experiment on the acorn oil content of phenolic compounds has been reported, the reliability of the results in the present study is difficult to establish. However, a related review of the literature depicts that the usual value for virgin olive oil ranges between 100 and 300 mg kg -1 (Andrewes et al, 2003). This indicates that the acorn oils contain significant amounts of phenolic compounds.…”
Section: Characterization Of Acorn Fruit Oils Extracted From Selectedmentioning
confidence: 99%